A escolha democrática dos gestores da escola pública: o caso do estado de Santa Catarina - Benjamini, Josseane (2024)
The present study emerges from the interest in understanding the environment and the actions of education professionals in the school context, with special attention to the participatory process in an education based on legal principles. The question that guides the research is formulated as follows: How the process of choosing managers in schools occurs public institutions in the State of Santa Catarina and what are the democratic consequences of this practice in school management? Our central focus is the election of school principals in schools states of Santa Catarina, highlighting Democratic Management as a key element. We adopted a qualitative methodological approach, based on a survey bibliographical, exploring works that address concepts related to school management democracy, community participation and the consequences of director elections. The bibliographic review aims to understand different perspectives, challenges and associated benefits to the democratic choice of directors, especially highlighting context-specific nuances Santa Catarina. When approaching Democratic Management at school, we historically contextualize the Democratic Management in Santa Catarina, exploring gains, benefits and possibilities associated with this approach in public schools. Divided into structured sections, the work includes introduction, school management, the gains and benefits of Democratic Management in public school and final considerations. Authors such as Libâneo (2007), Paro (2003), Lima (2018) and Souza (2007) to support our analysis. The inclusion of perspectives of these authors allowed a richer and more detailed analysis, contributing to a deeper understanding of the processes and results of Democratic Management in schools public. The research revealed that, although the election of directors represents progress for the strengthening democratic management, there are still major challenges related to its full implementation. We conclude that this practice contributes to more efficient school management. inclusive, approved to the desires and needs of the school community, providing valuable subsidies for the formulation of educational policies external to the promotion of a democratic and equitable management.